IMPLEMENTASI FRAMEWORK YII2 PADA SISTEM ELECTRONIC ARSIP (E-ARSIP) KEPENDUDUKAN NAGARI BALAH HILIA - Maharani Hamidah; Kasman Rukun (Universitas Negeri Padang, 2019)
This study aims to design and build a village electronic e-archive system. With the village population e-archive system, efforts to help manage outbound mail administration data become more systematic. So that data stored systematically will be easier to find, without slow access constraints due to poor file management. This system is designed using the framework yii2 with the concept of Model View Controller (MVC), PHP programming language, and MySQL. The result of this design is a system that runs on a browser software, and is only used by the Nagari Balah Hilia Office. This population e-arschive system provides an autocomplete feature that makes it easy for operators to find population data based on Population Identification Number (NIK), so that making outgoing mail becomes more effective, efficient, and Systematic.Keywords : Archive, E-Archive, Yii2 Framework, Autocomplete Feature